Unveiling the Food and Income Insecurity among Farm Households of Lucknow, Uttar Pradesh (Indian Journal of Extension Education, 2023)
The study was conducted during 2022-23 to assess the level of food insecurity and income status among farm households. Data from 474 farmers through personal interview method were collected. Agriculture was the primary occupation for most households followed by off-farm activities. Average per capita annual income (Rs. 1,00,073) was lower than the national average. The per capita annual income was Rs. 73,303, Rs. 93,256 and Rs. 1,44,456 for marginal, small, and medium farmers, respectively. About 47 per cent of the expenditure was made on consumption. A comparison of calorie intake to recommended calorie intake indicated that food insecurity was prevailing among 26 percent of the farmers. The major contribution to calorie intake was from cereals, the consumption of vegetables and fruits was low. A decision tree model using machine learning algorithms was used to identify the factors influencing food security. Per capita income, family size, consumption expenditure, social participation, and land holdings had significant importance in classifying the households as food secure and insecure. Diversifying farm activities and creating additional opportunities in rural areas, teaching households about balanced diets, promoting home gardening, and institutional policies to improve food security may be the strategic points.